Synthesis, Antibacterial and Cytotoxic Activities of New Thiazole Based Pyrrolidine Derivatives - Kocabas, Erdal; Sariguney, Ahmet Burak; Erci, Fatih; Cakir-Koc, Rabia; Kocabas, Hilal Ozen; Torlak, Emrah; Coskun, Ahmet (BIOINTERFACE RESEARCH APPLIED CHEMISTRY, 2021)
In this study, some thiazole-based pyrrolidine derivatives were synthesized, characterized by FT-IR and H-1 NMR spectroscopic techniques, and evaluated as potential antibacterial agents. Their antibacterial activities were evaluated by broth microdilution method and expressed as minimum inhibitory concentration; against Escherichia coli, Salmonella typhimurium, Bacillus cereus, and Staphylococcus aureus. Cytotoxicity studies of synthesized compounds were also conducted to minimize the toxic effects on healthy mammalian cells. From synthesized compounds, 4-F-phenyl derivative compound (11) has been found to inhibit Gram-positive bacteria with minimum toxicity selectively.
Keywords: thiazole; pyrrolidine; antibacterial activity; cytotoxicity; Chemistry